Systemic and oral alterations associated with stress in nurses of public referral hospital - Danilo Rodrigues; Dagmar de Paula Queluz (Universidade Estadual de Campinas, 2015)
Jobs that require great responsibility can cause serious damage to the body such as stress and its consequences. Stress can be one of the triggers of disease systemic and oral diseases in different professionals. Aim: To associate emotional stress with the systemic and oral alterations in the nurses of public referral hospital. Methods: All 60 nurses of both genders, with higher education level, different ethnicities and ages were invited to join this study. Nurses filled out the Inventory of Stress Symptoms for Adults (ISSL) and questionnaire of diseases/psychosomatic symptoms. Next, they were subjected to a stomatological examination of the oral cavity, according to the Boraks (1996) criteria. Stress was associated with most outstanding psychosomatic and oral variables by the Fisher's exact test for calculating the p value (0.05). Results: The sample was comprised of 37 nurses, most of them female (91.9%), young (83.7% are less than 36-years old), full range 22- 50 years old, white ethnicity (86.5%). The level of stress in level II (resistance) and III (exhaustion) was observed in 51.3% of the nurses. Symptoms of headache and gain of body weight lately were present in 48.6% of the nurses. With regard to oral alterations, 32.4% reported cold sore sometimes and 59.5% nibbled mucosa always. There was no significant association between the stress and psychosomatic and oral variables. Conclusions: Based on the results of this study it may be concluded that the nursing profession can lead to emotional stress, although no significant association between stress and disease/psychosomatic and oral symptoms was found. Future studies should be performed to evaluate this association.